THE RELATIONSHIP OF DIURETIC THERAPY AND CLINICAL OUTCOME ON QUALITY OF LIFE OF PATIENTS WITH CONGESTIVE HEART FAILURE - Najmiatul, Fitria; Nurul Zuhanna, Fachri; Rahmi Yosmar (Malaysian Journal of Public Health Medicine, 2023)
Congestive Heart Failure (CHF) has an impact on decreased quality of life and is the main cause of mortality and morbidity. To measure therapeutic goals and clinical outcomes, it is necessary to carry out a Health Associated Quality of Life (HRQoL) assessment. The study aimed to examine the relationship between diuretic therapy and clinical outcomes on the quality of life of patients with CHF. This descriptive-analytical study with a cross-sectional approach out was carried out at the Cardiology Polyclinic, Dr. M. Djamil Hospital in Padang. The Indonesian version of the Minnesota Living with Heart Failure Questionnaire (MLHFQ) was used and validated previously. The main clinical outcome was peripheral edema. A total of 98 CHF patients participated in the study. Data on diuretic therapy, clinical outcomes, quality of life, and patients’ sociodemographics were obtained from questionnaires and medical records. The Kruskal-Wallis and Mann-Whitney tests were used to analyze the relationship between diuretic therapy and clinical outcomes on patients' quality of life. Based on sociodemographics, most patients with congestive heart failure were male (66.3%), aged ? 60 years (51%), high school education level (38.8%), and retired (26.5%). The quality of life of patients with predominant CHF is of good quality (65.3%). The most common features of diuretic therapy were the combination of furosemide and spironolactone (54.1%) and the main clinical outcome was the presence of peripheral edema (53.1%). In conclusion, there is a substantial connection between diuretic therapy and the clinical effect (peripheral edema) on the patient's quality of life (p<0.05).